Philosophical Approaches to Moral Education: A Qualitative Study in Secondary Schools - Maharani (Mauve Journal De Leardu, 2025)
Moral education plays a vital role in shaping students’ character and ethical participation in society. This study investigates how philosophical approaches virtue ethics, duty-based ethics, and care ethics are implemented in Indonesian secondary schools. A qualitative multiple case study design was employed, involving interviews with teachers, students, and administrators, classroom observations, and document analysis across four schools in Jakarta. The study found that public schools emphasize virtue ethics, private schools adopt duty-based ethics, and faith-based schools often combine or focus on care ethics. These philosophical orientations influenced the teaching strategies used in schools, including storytelling, case studies, rule enforcement, and service learning. Students reported higher engagement with methods involving experiential learning. However, challenges such as parental pressure for academic performance, limited resources in public schools, and value conflicts in multicultural classrooms hindered the effective implementation of moral education. The study concludes that a blended approach, incorporating elements of virtue, duty, and care ethics, offers a more inclusive and effective framework for moral education. This approach prepares students for responsible citizenship in a pluralistic society and provides a foundation for future research on moral education in diverse contexts.